Novel protocol for multiple-dose oral administration of the L-type Ca2+ channel blocker isradipine in mice: A dose-finding pharmacokinetic study - Tamara Theiner; Nadine J. Ortner; Herbert Oberacher; Gospava Stojanovic; Petronel Tuluc; Jörg Striessnig (Channels)
Studies in genetically modified animals and human genetics have recently provided new insight into the role of voltage-gated L-type Ca2+ channels in human disease. Therefore, the inhibition of L-type Ca2+ channels in vivo in wildtype and mutant mice by potent dihydropyridine (DHP) Ca2+ channel blockers serves as an important pharmacological tool. These drugs have a short plasma half-life in humans and especially in rodents and show high first-pass metabolism upon oral application. In the vast majority of in vivo studies, they have therefore been delivered through parenteral routes, mostly subcutaneously or intraperitoneally. High peak plasma concentrations of DHPs cause side effects, evident as DHP-induced aversive behaviors confounding the interpretation of behavioral readouts. Nevertheless, pharmacokinetic data measuring the exposure achieved with these applications are sparse. Moreover, parenteral injections require animal handling and can be associated with pain, discomfort and stress which could influence a variety of physiological processes, behavioral and other functional readouts. Here, we describe a noninvasive oral application of the DHP isradipine by training mice to quickly consume small volumes of flavored yogurt that can serve as drug vehicle. This procedure does not require animal handling, allows repeated drug application over several days and reproducibly achieves peak plasma concentrations over a wide range previously shown to be well-tolerated in humans. This protocol should facilitate ongoing nonclinical studies in mice exploring new indications for DHP Ca2+ channel blockers.